Conflictual Practice Sharing in the MNC: A Theory of Practice Approach. Issue 9 (September 2016) - Bjerregaard, Toke; Klitmøller, Anders
This article advances a theory of practice approach to the study of conflictual practice sharing in the multinational corporation (MNC). The article demonstrates distinct opportunities offered by practice theory in researching the multiple lines of conflict and cooperation over local organizational practices, policies and strategies that emerge in the face of global HQ demands. Extant literature concentrates on how transfer outcomes are shaped by institutional or cultural distance at the national level and inter-unit relationships, often taking the subsidiary as a unit of analysis. Therefore, intra-unit conflicts over global practice sharing are under-researched, particularly how such conflicts are shaped by actors' differential situatedness in the immediate societal context of the subsidiary. In explicating a practice theory agenda for the study of MNCs, we contribute to an understanding of how actors' social positioning within and outside the firm, combined with their career opportunities, shape both the character and dynamics of intra-unit conflicts over the local configuration of organizational practices mandated by HQ. Building on an extended case study of an MNC in a Mexican special economic zone (SEZ), we thus examine how subsidiary actors accommodate, actively support and resist various parts of an HQ-mandated management control system.